Num8ers - Ward, Rachel 1964- (Chicken House, Scholastic, 2010)
Fifteen-year-old Jem knows when she looks at someone the exact date they will die, so she avoids relationships and tries to keep out of the way, but when she meets a boy named Spider and they plan a day out together, they become more involved than either of them had planned.